Infant deaths related to cardiac malformations in the Northeast of Brazil: an ecological study (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile about infant deaths caused by cardiac malformation in the state of Maranhão. Method: This is a retrospective, descriptive, quantitative approach and epidemiological study of infant deaths from cardiac malformations in the period 2016-2020. The data were collected through the National System of Notifiable Diseases (SINAN), available through the Department of Informatics of the Unified Health System (DATASUS). Results and Discussion: The year 2017 showed the highest incidence of deaths, totaling 119 infant deaths, presenting the percentage of 21%. The male gender stood out with the highest predominance of deaths, achieving a percentage of 54.10% in relation to the total number of cases. Brown individuals had the highest incidence of infant deaths, obtaining 359 deaths, equivalent to 65.21% of cases. Regarding birth weight, most deaths in individuals who were born weighing between 3000g and 3999g, about 183 deaths (33.33%). Conclusion: The results acquired in this research reveal a high and worrisome incidence of this grievance in males, within the binarity, besides its high expression in people of mixed race.